Comparison Of The Customary Legal System And The National Legal System: The Case Of Arrested Marriage In Sumba, East Nusa Tenggara - Dhani Kristianto; Ade Saptomo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the comparison between the Customary Legal System and the National Legal System in the context of legal practice related to arrest marriage cases in Sumba, East Nusa Tenggara. The main focus of this research is to understand how these two legal systems interact and influence each other, especially in handling cases of arrested marriages involving the people of Sumba. The Customary Law System in Sumba has unique and traditional norms relating to captive marriages, which often differ from the norms found in the national legal system. This gap creates challenges in enforcing the law and protecting individual rights, especially for the women involved in the cases. This study contributes to our understanding of the complex dynamics between the Customary Legal System and the National Legal System in Indonesia, by providing in-depth insight into the implementation of the law in the context of arrest marriage cases. The implications of this research can be used as a basis for revising or developing legal policies that are more inclusive and just at the local and national levels.